Diskurs sovremennoj detskoj literatury - Beloglazova, Еlena V. (Stylistyka, 2021)
The author article "Discourse of the modern children's literature in the light of interdisciplinary approach" Elena V. Beloglazova sets the goal of illustrating the potentia! of interdisciplinary analysis